Ukrainian export and production after the 2014 Russia shock - Daria Suprunenko (Osnabrück University, Institute of Empirical Economic Research, 2024)
While significant attention has been dedicated to sanctions episodes among major economies which usually rely on a diverse set of trade partners, little is known about the impact of sanctions imposed by senders on economies highly dependent on them. Using Ukrainian export data for 2009-2019 at product level, I study the effects of trade restrictions imposed by the Russian Federation against Ukraine since 2016 accounting for the impact of Russian occupation and destruction of productive capacities. I find no evidence for evasion of Russian trade policy measures via export to other members of the Eurasian Economic Union or product misclassification, instead trade flows were redirected to new destinations. Industries with higher exposure to Russian market experienced significant reductions in employment, number of enterprises and turnover when targeted by embargo.
Keywords: F13; F14; 330; Ukraine; Russia; sanctions; trade war